Combination Therapies with Ablation: Immunoablation - Kolarich, Andrew R.; Theodoulou, Iakovos; Georgiades, Christos (Digestive Disease Interventions, 2020)
Percutaneous ablation has been increasingly utilized as an alternative or adjunct to surgical resection of solid tumors. However, high rates of local recurrence and disease progression both with resection and ablation, particularly in patients with primary and metastatic liver malignancies, have limited further extension of overall survival. Systemic oncology treatment has progressed beyond traditional chemotherapeutic agents to immunotherapeutic agents that exert their effect by enhancing the body's immune response against cancer cells. The induction of necrotic cell death and the release of a large number of tumor antigens as a result of ablation have stimulated interest in combination therapy as a potential method of improving response to immunotherapy. This review focuses on the current scientific evidence for combination therapy of immuno-oncologic agents and locoregional ablation techniques.
Keywords: immunotherapy; interventional oncology; ablation; cancer